Using the exp-log technique,
![\displaystyle \lim_(n\to\infty) \frac{\left(1 * 2^2 * 3^3 * \cdots * n^n\right)^{\frac1{n^2}}}{n^{(n+1)/(2n)}}](https://img.qammunity.org/2023/formulas/mathematics/college/q1v2abbggj2591lusdzineo6bfhybz3js0.png)
![\displaystyle = \exp\left(\lim_(n\to\infty) (\ln\left(\prod\limits_(k=1)^n k^k\right))/(n^2) - (n+1)/(2n) \ln(n)\right)\right)](https://img.qammunity.org/2023/formulas/mathematics/college/rvkfubq08s7y547ogpl5ixptloabiqv950.png)
![\displaystyle = \exp\left(\lim_(n\to\infty) (\sum\limits_(k=1)^n k\ln(k))/(n^2) - (n+1)/(2n) \ln(n)\right)\right)](https://img.qammunity.org/2023/formulas/mathematics/college/oweiv6ka0i0rnl3ewik273rvofre4svhxe.png)
We have ln(k) = ln(k/n) + ln(n), and so we can rewrite the limand as
![\displaystyle = \exp\left(\lim_(n\to\infty) \left(\frac1n \sum\limits_(k=1)^n \frac kn \ln\left(\frac kn\right) + (\ln(n))/(n^2) \sum_(k=1)^n 1 - (n+1)/(2n) \ln(n)\right)\right)](https://img.qammunity.org/2023/formulas/mathematics/college/jynjr0nvyp3vlg15h1276nk2lkl5zmetg8.png)
Then the first sum converges to a definite integral,
![\displaystyle \lim_(n\to\infty) \frac1n \sum_(k=1)^n \frac kn \ln\left(\frac kn\right) = \int_0^1 x \ln(x) \, dx = -\frac14](https://img.qammunity.org/2023/formulas/mathematics/college/govntvaoeonm8mkt86a0dlwdoubg17490p.png)
while the remaining terms vanish since
![\displaystyle (\ln(n))/(n^2) \sum_(k=1)^n 1 = (\ln(n))/(n^2) * \frac{n(n+1)}2 = (n+1)/(2n)\ln(n)](https://img.qammunity.org/2023/formulas/mathematics/college/gnl1jkplwakwtz6s0au5vulyqjjm4ljolp.png)
So the limit is
.
Since
![\frac1{x(x+1)} = \frac1x - \frac1{x+1}](https://img.qammunity.org/2023/formulas/mathematics/college/yfms2scpl5bv48alabr9wpf46zoxo5tos6.png)
it's easy to show that the integral reduces to
![\displaystyle \int_k^(k+1) (k+1)/(x(x+1)) \, dx = (k+1) \ln\left(((k+1)^2)/(k(k+2))\right)](https://img.qammunity.org/2023/formulas/mathematics/college/q6yc2lnpdfbleu3k1b5rg51ohpzqu1o0po.png)
so we can write the sum as
![I = \displaystyle \sum_(k=1)^(98) \int_k^(k+1) (k+1)/(x(x+1)) \, dx = \sum_(k=2)^(99) k \ln\left((k^2)/(k^2-1)\right)](https://img.qammunity.org/2023/formulas/mathematics/college/1tky3x1w2cdo419oa2o9ryogdvih1nzwmj.png)
We have k²/(k² - 1) > 1 for all k, so that ln(k²/(k² - 1)) > ln(1) = 0. We can see the first 3 terms of the sum already exceed 1 > 49/50, so (D) is true.
Numerical computation of the sum suggests I < ln(99), but I have yet to come up with an analytical solution for this bound...